CHARACTERISTIC COMPARISON OF CATFISH(Hemibagrus nemurus) FROM WILD, POND CULTURE, AND CAGE - Iskandar, Dedi; Hasan, Bustari; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aims to evaluation and compared chemical proximate compositions, NPN, amino acid and fat acid of Hemibagrus nemurus from wild catfish, pond culture and cage. Catfish used is 70 from wild (Kampar river), pond culture, and cage in Paku river, Kampar.Value of catfish was evaluation, value of edible portion, dressing percentage water holding capacity,sensory quality, proximate, non protein nitrogen, amino acid, and fat acid. The research was showed edible portion, dressing percentageand sensory quality was not different between fish habitat,water holding capacity highest was catch from pond culture, followed by fish from cage and wild,protein compositions, and cinder fish from wild was highest, next followed by fish from cage and pond culture. Fat acid contents fish from pond culture more hight of the cage and wild, water contents fish from cage and wild more hight of the pond culture, NPN highest was catch from wild, followed by fish from cage and pond culture. Base on data obtained, it was concluded that amino acid was not different from fish habitat. Fat acid of PUFA more hight on fish cage compared pond culture and wild catch.Keywords : Hemibagrus nemurus, habitat, cage, wild catch, pond culture